Tecnologia social: tecendo novos caminhos para a prática interventiva do Serviço Social - ABREU, Keila Helena Garcez (2022)
Social Technology (TS) is an innovative tool applied in socially vulnerable communities to respond to the latent expressions of the social issue. The bias of this interdisciplinary work permeates the knowledge of technology and Social Work. This scientific production has the central purpose of disseminating the ST category as possibilities for the interventional practice of Social Work from the interaction with technology. It started with the following question: The phenomenon of technology fits the developmentalist discourse, however, how can Social Work be associated with the interventional work of ST? In view of this, a space with fundamental importance of the systematized study opens up for new possibilities of TS in the academic and professional field. For the methodological process, it started with a bibliographic research, document analysis, application of a semi-structured questionnaire with the CSO (Civil Society Organization) Avante, which develops the TS in its community projects. It concludes with the production of the ebook entitled “Social Technology: a connection between Technology and Social Service”, product of this work. We sought to build a base support material for the knowledge and use of this tool, which will serve as an aid for scholars and professionals, especially Social Work, with the aim of developing innovative interventions in their professional instrumentality.